EMPLOYEE LOYALTY: PERAN TRUST IN MANAGEMENT DAN PEERS DENGAN MEDIASI EMPLOYEE SATISFACTION - Dimas Fitrah Rahmatika (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to determine the effect of trust in management and trust in colleagues on employee loyalty which is mediated by job satisfaction in employees of one of the state-owned companies in Surabaya. This research uses the Structural Equation Modeling (SEM) analysis method using the smartPLS 3.0 application. The sample used in this research was 45 respondents using a purposive sampling method, namely distributing questionnaires online to respondents who met certain criteria. The research results show that employee satisfaction, trust in management, and trust in colleagues have a positive and significant effect on employee loyalty. However, the variables of trust in management and trust in colleagues have a direct effect but not significant on employee loyalty.